Comparison between women's and men's game at rugby Worlc Cup level - Vaz, L.; Mouchet, A.; Carreras, D. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
No study has accounted for the comparison between women´s and men´s game at rugby world cup level. The rugby men`s game has developed since 1995, so has the women`s game, but while the women`s game is structurally similar to that played by men in RWC 99. The aim of this study is to determine if any relationship exists between women´s and men´s game at rugby world cup level. Archival data report to game-related statistics from thirty matches played in Women´s RWC 2006 and forty-eight matches played in Men´s RWC 2007. We analyzed and compare matches during the different stages (pool, knockout and final stages) of RWC finalist countries. The statistical review and match analysis are analysed to help identify the most powerful game-related statistics to discriminate the game. In women´s RWC 2006 the average number of points per match was 39. 179 tries were scored in the 30 matches and there were six times more tries than penalty goals. The activity cycles: ball in play time averaged 41%, rucks/mauls averaged 131 per game, passes averaged 220 per game and almost 80% of all passing movements contained 2 passes or less. Open play kicks averaged 43 per game. Women set pieces: average 31 lineouts per game, 68% were contested and possession was retained on 73% of occasions. There were an average of 28 scrums per game and the possession retained was 89%. In men´s RWC 2007, the average number of points scored per match was 52. In RWC 296 tries were scored in the 48 matches, average 6.2 tries per game. 32% of tries came from lineout possession, 18% from scrum, 17% came from turnover or handling error and 15% came from opponents kick. The men´s activity cycles: ball in play time averaged was 44%, the men`s game produces 40% more rucks and mauls and around 35% more passes, average 144 per game. The men´s set pieces were lineout also average 31 per game just over 60% were contested and possession was retained on 80% of occasions. There were only 19 scrums per game/RWC 2007 some 9 more than in the Women`s RWC 2006. Apart from scrums - which were 33% more frequent in the men`s game, all core elements were recognizably the same, but with one significant exception - kicking. While the average number of tries were similar, when it came to kicks there were huge differences between the men`s game and the women`s game. Kicking therefore was a far less noticeable part of the women`s game with fewer kicks at goal, a lesser success rate and fewer kicks from hand during open play. What is clear therefore is that kicks at goal are less frequent and less successful than in the men`s game. This also illustrates the fact that kicks over a certain distance cause considerable difficulty to many women`s teams. There are some common tendencies in men´s and women´s game at rugby world cup level. The various teams may find the data of benefit in establishing benchmarks and performance indicators for future tournaments.